The effects of problem-based learning (PBL) on undergraduate medical students’ critical thinking and communication skills development: A scoping review across resource-rich and resource-limited settings (2015–2024) - Bruce Ayabilla Abugri; Maxwell Ateni Assibi; Anthony Amalba; Patience Kanyiri Gaa; Sophia E.A. Kpebu; Patience Afua Adwaapa Karikari; Victor Mogre (PLoS ONE, 2026)
Background Problem-based learning (PBL) is widely recognized as an effective method for enhancing critical thinking and communication skills in medical education. However, in first-year medical students, the specific and detailed effects have yet to be explored, especially across resource-rich and resource-limited educational settings. Objective The scoping review evaluates the effects of problem-based learning on the development of critical thinking and communication skills of first-year medical students and compares the effectiveness of the method in resource-rich and resource-limited environments. Methods This scoping review followed Arksey and O’Malley’s framework. A systematic search of the literature was conducted on Google Scholar, PubMed, and ProQuest for studies published between 2015 and 2024. Included studies were screened according to the defined criteria, and data were extracted on study characteristics, interventions, and outcomes measured. Results A total of eight studies were found that met inclusion criteria: only one among them exclusively studied first-year students. The results of this cross-sectional study (with a descriptive self-report questionnaire) found that first-year students have a positive attitude toward PBL since they reported the following: high engagement (97%) and improved teamwork (87%). The included studies reported that PBL was associated with perceived improvements in critical thinking and communication skills among undergraduate medical students in both resource-limited and resource-rich educational environment. There were methodological variations, and some regions were entirely unrepresented. All the reviewed studies were published in Asia, with no studies from Africa. Conclusion The reviewed studies suggest that PBL may be associated with perceived improvements in critical thinking and communication skills; however, findings remain tentative due to methodological and contextual limitations.